Looking Into the Abyss—How Many Species of Biting Midges (Diptera: Ceratopogonidae) Are There? Their Remarkable Diversity in Costa Rica and Elsewhere - Borkent, Art; Spinelli, Gustavo R.; Díaz, Florentina; Steinke, Dirk; Perez, Kate H.j.; Stur, Elisabeth; Hallwachs, Winnie; Janzen, Daniel H. (Zootaxa, 2024)
The biting midges (Ceratopogonidae) are one of the most species-rich families of insects on the planet with over 6,200 named species. However, their true diversity is unknown and this paper is the first to address the question. Our systematic study of the family in Costa Rica indicates that 192 species were present in a four hectare area of cloudforest at Zurquí de Moravia, at 1,600 m after a year of intensive sampling. Combined with a collection from a single Malaise trap at Tapantí for one year, about 40 kms away and also at 1,600 m, the total was 245 species with significant differences between the two areas and with the strong majority unnamed. This compares to 430 named species for all of Costa Rica and 1,314 for the entire Neotropical Region. Barcoding of 221,407 specimens from Costa Rica similarly indicates large numbers of unnamed species with 4,023 BINs present. On this basis, we project at least 5,000 species in Costa Rica and using ratios of named species here and elsewhere, we suggest that nearly 73,000 are present worldwide. Details from Malaise traps in the Área de Conservación Guanacaste also indicate various levels of endemism. Samples from Bolivia support an interpretation of high diversity. The diversification of the family was examined by comparing phyletic lineages, rather than merely comparing numbers of species in various genera, providing insight as to why some lineages are more diverse than others. Zoogeographic patterns of named species suggest stronger southern connections for Costa Rican Ceratopogonidae in both cloudforest habitats as well as the country as a whole, although many are also more broadly distributed north and south of the country. Comparisons between various collecting methods at Zurquí de Moravia indicate the efficacy of Malaise traps but also the importance of light traps and other methods in sampling adults of Ceratopogonidae. Phenological data from the Malaise traps in the Área de Conservación Guanacaste suggest some patterns of emergence of adults in Costa Rica, the first for any tropical country anywhere.